How can the role of leachate on nitrate concentration and groundwater quality be clarified? An approach for landfills in operation (Southern Italy). (July 2018) - Cossu, Raffaello; Zuffianò, Livia Emanuela; Limoni, Pier Paolo; De Giorgio, Giorgio; Pizzardini, Paola; Miano, Teodoro; Mondelli, Donato; Garavaglia, Roberto; Carella, Carmine; Polemio, Maurizio
Highlights: Isotope methods reveal fertilisers as main nitrate groundwater source. Mineralogical method reveals residual soil particles as source of metals. Multi-methodological approach able to discover groundwater-leachate mixing. Approach and results absolve leachate reassuring population and institutions. Abstract: Where the unique natural water resource is groundwater, the attention and the susceptibility of local communities and authorities to groundwater quality degradation risks can be so high to determine relevant problems to waste management, especially for landfills in operation or to be realised. A multi-methodological approach was suggested with the purpose to clarify the role of landfill leakage on groundwater quality degradation. The selected study area (SSA) hosts some landfills in a narrow portion of a wide and deep coastal karstic aquifer, for these characteristics to be considered a case of high hydrogeological complexity and vulnerability. News concerning nitrate and secondly iron groundwater concentration anomalously high caused concern in the population and strong local opposition to landfills. The multi-methodological approach includes: the hydrogeological site characterization; the chemical study and the multi-isotope characterization of groundwater and leachate; the land use analysis and the estimation of nitrogen contributions deriving from fertilizers; the mineralogical study of groundwater suspended particles to define the role of natural soil substances. The hydrogeological site characterisation highlighted the local peculiarities of the aquifer. The chemical study was used to define geochemical features, groundwater and leachate characteristics and their macroscopic mixing. The environmental isotopes of hydrogen, carbon, nitrogen, and oxygen were used to investigate the groundwater origin, the most relevant geochemical reactions, the existence of groundwater-leachate mixing, and the sources of anthropogenic NO3 − . The land use analysis highlighted quantity and type of used fertilizers permitting to compare these with groundwater in terms of isotopic signature. The mineralogical study demonstrated the role of suspend natural particles due the presence of terre rosse (red or residual soils) in groundwater. The approach confirmed that there are not the groundwater quality degradation effects of landfills, contributing to reassure population and institutions, simplifying the waste management.